2010
DOI: 10.2320/matertrans.m2009333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conditions of Unidirectional Solidification on Microstructure and Pore Morphology of Al-Mg-Si Alloys

Abstract: Aluminum and Al-Mg-Si alloy ingots with pores were fabricated by unidirectional solidification through thermal decomposition of Ca(OH) 2 powders. The porosity of aluminum and Al-Mg-Si alloy were 10-17% and 0.1-2%, respectively. While the pores with 250-400 mm diameter were observed in a grain or across several grains in the aluminum ingots, smaller pores with 50-300 mm were observed in an eutectic region between primary dendrites in the Al-Mg-Si ingots. In the alloys with Mg(0.25-0.5 mass%) and Si(0.2-0.4 mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This is the interpretation previously suggested by Spierings et al [36] for a similar observation in SLM stainless steel 316L. Conversely, other work on Al-Mg-Si alloys by Kim et al [58] and Al-Mg alloy by Fang et al [59] has shown that larger pores result from lower cooling rates.…”
Section: Accepted Manuscriptsupporting
confidence: 86%
“…This is the interpretation previously suggested by Spierings et al [36] for a similar observation in SLM stainless steel 316L. Conversely, other work on Al-Mg-Si alloys by Kim et al [58] and Al-Mg alloy by Fang et al [59] has shown that larger pores result from lower cooling rates.…”
Section: Accepted Manuscriptsupporting
confidence: 86%
“…The liquidus and solidus temperatures for [6]. Castings for a military application, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The peritectic microstructure is the finest among the three transfer velocities, which is consistent with a gereral relationship between the microstructure and solidification velocity. 15,16) The precipitates indicated by the arrow are also finest and distributed homogeneously in the matrix. 17) EPMA and XRD measurements were performed to identify the precipitates.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the primary crystals are more easily formed at high transfer velocity. 15,16) The formed primary crystals possibly suppresses the decrease in the porosity at high transfer velocity, because the crystals would suppress the escape of hydrogen from the solid/liquid interface. As a result, in porous Al-Ti alloy, the porosity possibly does not decrease at high transfer velocity.…”
Section: Effect Of Transfer Velocity On Porositymentioning
confidence: 99%